Alexander Graham Bell : Making Connections. - Pasachoff, Naomi (Oxford Portraits in Science Ser., 1996)
Alexander Graham Bell forever changed the world. The telephone and his many other landmark inventions rank among the most transforming and enduring of the modern era. But it was his work with the deaf, teaching as well as inventing tools to ease communication, that he considered his life's work.